Health Perceptions and Attitudes Toward Cancer Screenings Among Individuals Attending Family Health Centers: A Cross-Sectional Research - Dilek Yıldırım; Ferda Akyüz Özdemir; İbrahim Halil Boyacı (İstanbul Gelişim Üniversitesi Sağlık Bilimleri Dergisi, 2026)
Aim: This study aimed to investigate the effect of individuals’ health perceptions on their attitudes toward cancer screening and to examine the relationship between these two variables.Method: We implemented a descriptive, cross-sectional, and correlational design. The sample consisted of 351 adults who applied to a family health center in Muğla, Turkey, between January and August 2025. Data were collected using a Personal Information Form, the Health Perception Scale, and the Attitude Scale for Cancer Screening. Statistical analyses included descriptive tests, independent samples t-tests, Pearson correlation, and regression analysis.Results: The mean age of participants was 43.4±13.9 years, and 60.1% had never undergone cancer screening. The average scores were 38.17±8.21 on the Health Perception Scale and 74.64±15.89 on the Attitude Scale for Cancer Screening. A significant positive correlation was found between health perception and attitudes toward cancer screening (r=0.350, p<0.001). Regression analysis demonstrated that health perception explained 12.3% of the variance in screening attitudes. Participants with knowledge about cancer or screening methods had significantly higher health perception scores (p<0.05). No significant differences were observed in screening attitudes by gender, age, or chronic disease status.Conclusion: The findings indicate that health perception is a key determinant of attitudes toward cancer screening. Interventions that strengthen health literacy, enhance awareness, and reduce psychosocial barriers could increase participation in screening programs. Educational initiatives and support interventions delivered through family health centers may play an essential role in promoting early detection and improving community health outcomes.